A clinical study of serum lipid profile in benign breast disease in a tertiary care hospital - M. S., Prabakar; Prakasam, Nithyaraj; S., Reshma; K., Loganathan; V., Palani (International Surgery Journal, 2019)
Background: The aim of the study was to evaluate an association of serum lipid profile in women with benign breast disease and to analyze a possible relationship between serum lipid profile and benign breast diseases with emphasis to laboratory findings. Methods: Hospital based study carried out at ACS Medical College, Chennai, during the period of June 2018 to November 2018. 75 women in General Surgery ward/outpatient were included in the study. Subjects included in the study were women of age between 16 to 35 years, provided they fulfilled inclusion and exclusion criteria. History was noted, serum lipid profile was done. Results were noted and analysed. Results: Out of 75 subjects, 21.3% of women with benign breast disease were having elevated serum lipid profile. Conclusions: It is concluded that benign breast disease is associated with altered serum lipid profile namely hyperlipidemia. Therefore, routine screening and treatment of this condition is must among women with benign breast disease by dietary management, use of anti-hyperlipidemic drugs to achieve long lasting cure and to prevent possible future recurrences.